Apocalypse now now - Human, Charles (Department of English Language and Literature, 2014)
Baxter Zevcenko is your average 16-year-old-boy. If by average you mean a possible serial killer, the kingpin of a porn-peddling schoolyard syndicate and the only thing standing in the way of full-scale gang warfare between the two powerful gangs which control Westridge High School. Which may well be what counts for average these days.